Ankylosed spines are prone to fracture. - Hunter, T. (College of Family Physicians of Canada, 1995)
Fracture of an ankylosed spine is often overlooked. Because the force that damages an ankylosed spine is frequently slight, patients do not realize they are injured. Doctors can miss the fracture for the same reason and because patients already have a history of back pain. Plain radiographs sometimes fail to demonstrate the fracture site.